Effect of Mn doping on the low-temperature synthesis of tricalcium phosphate (TCP) polymorphs. Issue 10 (August 2019) - Sinusaite, Lauryna; Renner, Alexander M.; Schütz, Markus B.; Antuzevics, Andris; Rogulis, Uldis; Grigoraviciute-Puroniene, Inga; Mathur, Sanjay; Zarkov, Aleksej
Abstract: Effect of Mn doping on the low-temperature synthesis of tricalcium phosphate (TCP) polymorphs was demonstrated in α- and β-TCP polymorphs prepared by wet precipitation method under identical conditions and annealed at 700 °C. Calcium phosphates with Mn doping level in the range from 1 to 5 mol% were studied and the formation of desired polymorph was controlled by varying Mn content in as-prepared precipitates. It was found that increasing Mn content resulted in the formation of β-TCP, while α-TCP was obtained with low Mn doping level, whereas a mixture of two polymorphs was obtained for intermediate Mn concentrations. Moreover, doping with Mn ions allowed the synthesis of β-TCP at relatively low temperature (700 °C). Synthesized compounds were characterized by X-ray diffraction (XRD) analysis, electron paramagnetic resonance (EPR), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), inductively coupled plasma optical emission spectrometry (ICP-OES) and colorimetric MTT assay.